2022
DOI: 10.3390/molecules27175387
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Zn2+-Pre-Intercalated V2O5·nH2O/rGO Composite with Boosted Electrochemical Properties for Aqueous Zn-Ion Batteries

Abstract: Layered vanadium-based materials are considered to be great potential electrode materials for aqueous Zn-ion batteries (AZIBs). The improvement of the electrochemical properties of vanadium-based materials is a hot research topic but still a challenge. Herein, a composite of Zn-ion pre-intercalated V2O5·nH2O combined with reduced graphene oxide (ZnVOH/rGO) is synthesized by a facile hydrothermal method and it shows improved Zn-ion storage. ZnVOH/rGO delivers a capacity of 325 mAh·g−1 at 0.1 A·g−1, and this val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…S9 † demonstrate that, when compared to other vanadium-based materials utilized in AZIBs reported in recent years, it exhibits a remarkable advantage in terms of specic capacity. [31][32][33][34][35][36][37][38] Upon increasing the current density to 2.5 A g −1 , the absence of a distinct charge-discharge plateau in 3D VO x -V 2 CT x @rGO-30% can be attributed to its relatively dense interlayer distribution, which hinders the embedding and migration of zinc ions (Fig. 5c).…”
Section: Resultsmentioning
confidence: 99%
“…S9 † demonstrate that, when compared to other vanadium-based materials utilized in AZIBs reported in recent years, it exhibits a remarkable advantage in terms of specic capacity. [31][32][33][34][35][36][37][38] Upon increasing the current density to 2.5 A g −1 , the absence of a distinct charge-discharge plateau in 3D VO x -V 2 CT x @rGO-30% can be attributed to its relatively dense interlayer distribution, which hinders the embedding and migration of zinc ions (Fig. 5c).…”
Section: Resultsmentioning
confidence: 99%
“…A combined experimental and DFT study of ZnCo 2 O 4 showed that the oxygen vacancy formation can improve the Zn 2+ ion diffusion by enlarging channels [73]. A facile hydrothermal method was applied to prepare a composite consisting of Zn x V 2 O 5 and graphene oxide to form a stabilized structure and enhance the diffusion of Zn 2+ ions [74].…”
Section: Diffusion Of Zn 2+ Ionsmentioning
confidence: 99%
“…The dwindling reserves of fossil fuels and growing environmental awareness are driving the continued research on reliable large-scale battery systems for the storage and utilization of intermittent-generated renewable energy [ 1 , 2 , 3 , 4 , 5 ]. Lithium-ion batteries (LIBs) are the most extensively studied rechargeable batteries; however, they are not suitable for large-scale energy storage due to the scarcity of lithium resources and safety concerns [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%